The substitution of agrobased society for industrial society: A perspective of transforming societies - Hongyun Han; Sheng Xia (Global Journal of Ecology - Peertechz Publications, 2021)
Since the Industrial Revolution, a new era has arisen as the Anthropocene, in which human actions have become the main driver of global ecological crises outside the stable environmental state of the Holocene. During the Holocene, environmental change occurred naturally and Earth's regulatory capacity maintained the conditions that enabled human development. By contrast, oil-dependent industrial society has exerted ecological crises. Agrobased society, in which almost all demands of human can be supported by agriculture, might be the ultimate solution industrial society facing ecological crises, in which there is a paradigm shift from the general and unlimited economic growth pursued by virtue of oil dependence to agrobased growth. The substitution of agrobased society for industrial society is an evolutionary result of Negation, it is a negation of materialized industrial society. The core feature of agriculture is to use organisms as production objects and rely on life processes to achieve production goals. The substitution of agrobased society for industrial society is the precondition for a sustainable carbon cycle, breaking through resource shortage, alleviating the environmental pressure of economic development. Meanwhile, it is feasible for the substitution of an agro-based society for an industrial society associated with the development of bio technologies and environmental awareness.